Response of Ionospheric Profile Parameters to Equatorial Electrojet Over Peruvian Station. Issue 4 (24th April 2019) - Bello, S. A.; Abdullah, M.; Hamid, N. S. A.; Reinisch, B. W.; Yoshikawa, A.; Fujimoto, A.
Abstract: The response of the ionospheric bottomside electron density profile parameters of the F 2 layer, namely, the maximum electron density ( NmF 2), the maximum height of F 2 layer ( hmF 2), and bottomside thickness (B0) parameter to the equatorial electrojet (EEJ) current is examined for a Peruvian location at the Jicamarca station (12 °S, 76.9 °W) in the South American sector. The results of the analysis show that both hmF 2 and B0 increase for 2 h before sunrise and exhibit a postsunset peak during the equinoctial and summer months. The increase in the peak height, hmF 2, is observed to terminate before midday, while B0 continued to increase throughout the daytime. The apparent midday and postnoon peaks in NmF 2 occur in all the seasons under study. It was demonstrated that a relationship exists between EEJ and the profile parameters hmF 2 and B0 during low and moderate solar conditions. Conversely, the correlation coefficient between EEJ and NmF 2 is statistically significant only during solar minimum conditions but correlates poorly, if at all, with EEJ during moderate solar activity. Key Points: Different variability of EEJ and ionospheric profile parameters over Peruvian region during low and moderate solar epochs Daytime EEJ plays a role in the variability of the maximum height of the ionospheric F2 layer (hmF2) and thickness parameters (B0) Relationship between the ionospheric peak electron density (NmF2) with EEJ is solar dependent